2010
DOI: 10.1074/jbc.m110.102830
|View full text |Cite
|
Sign up to set email alerts
|

Vinculin Is a Dually Regulated Actin Filament Barbed End-capping and Side-binding Protein

Abstract: The focal adhesion protein vinculin is an actin-binding protein involved in the mechanical coupling between the actin cytoskeleton and the extracellular matrix. An autoinhibitory interaction between the N-terminal head (Vh) and the C-terminal tail (Vt) of vinculin masks an actin filament side-binding domain in Vt. The binding of several proteins to Vh disrupts this intramolecular interaction and exposes the actin filament sidebinding domain. Here, by combining kinetic assays and microscopy observations, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 55 publications
5
92
2
Order By: Relevance
“…In cells, multiple parameters can modify the activity of proteins, such as the charge of membrane lipids, the addition of phosphate groups by kinases, local gradients of pH and cations, crowding effects or the binding of partners. Hence, in many instances, it proved informative to screen a variety of physico-chemical conditions, including a mild reduction in ionic strength, before establishing the activity of actin-binding proteins such as formins, VASP or vinculin (5,31,32). Here, varying the ionic strength was sufficient to reveal a new inhibitory activity of ABD1 ( Figure 1A).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In cells, multiple parameters can modify the activity of proteins, such as the charge of membrane lipids, the addition of phosphate groups by kinases, local gradients of pH and cations, crowding effects or the binding of partners. Hence, in many instances, it proved informative to screen a variety of physico-chemical conditions, including a mild reduction in ionic strength, before establishing the activity of actin-binding proteins such as formins, VASP or vinculin (5,31,32). Here, varying the ionic strength was sufficient to reveal a new inhibitory activity of ABD1 ( Figure 1A).…”
Section: Resultsmentioning
confidence: 98%
“…Talin ABD1 inhibits actin filament barbed end elongation − To determine the ability of talin constructs to regulate actin assembly ( Figure S1A, C), we first monitored barbed end elongation by measuring the increase in pyrenyl-labeled actin fluorescence upon polymerization in the presence of spectrin-actin seeds (5). In cells, multiple parameters can modify the activity of proteins, such as the charge of membrane lipids, the addition of phosphate groups by kinases, local gradients of pH and cations, crowding effects or the binding of partners.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Aragona et al showed that knockdown of the F-actin capping or severing proteins CapZ, cofilin and gelsolin, increases F-actin bundling and promotes the nuclear localization of YAP/TAZ on soft ECM (Aragona et al, 2013). Interestingly, vinculin directly binds to Factin (Jockusch and Isenberg, 1981;Menkel et al, 1994) and has F-actin-bundling and -capping activities (Le Clainche et al, 2010;Wen et al, 2009). Here, we demonstrated that actin-bindingdeficient vinculin I997A (Thompson et al, 2014) lacks the ability to promote the change in the YAP/TAZ nuclear localization that is dependent on ECM stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increasing the binding of F-actin, vinculin might bring other factors to cadherin adhesions, such as members of the vasodilator-stimulated phosphoprotein (VASP) (Brindle et al, 1996) and ponsin families (Kioka et al, 1999;Mandai et al, 1999), as well as the ARP2/3 complex (DeMali et al, 2002;Tang and Brieher, 2012), to regulate Factin remodeling. Moreover, there is evidence that vinculin itself has an actin-polymerization activity in its tail domain (Le Clainche et al, 2010;Wen et al, 2009). Therefore, a forcedependent increase in actin polymerization at cell-cell junctions might serve to counteract the pulling force that is exerted by contractile F-actin.…”
Section: A-catenin and Vinculin -A Central Protein Pair In Cadherin Mmentioning
confidence: 99%